Goal-Driven Logistics—Shaping the Soccer Match Experience - Paché, Gilles (Journal of Organizational Psychology, 2025)
Crowd management at soccer matches—or “football” matches in Europe—presents significant logistical challenges that remain underexplored in supply chain academic literature. This gap is particularly notable given stadium access, internal venue layout, and post-event departure processes play a crucial role in shaping the fan experience. The interaction between logistical systems and psychological factors is essential in influencing the overall experience of thousands of attendees. This article delves into these dimensions, offering a comprehensive understanding of the complexities involved in managing large crowds in sports venues. Additionally, it proposes new research directions, particularly in examining how psychological insights can enhance crowd flow, safety, and fan satisfaction. By bridging the gap between logistics management and crowd psychology, this work opens innovative avenues for further exploration in event management and sports venue design. These findings have the potential to improve the soccer match experience for both clubs and fans, fostering a more seamless and enjoyable atmosphere that benefits all stakeholders.